Multisensory Phonics Via Smart TV Advances Early Reading In Slow Learners: Fonik Multisensori Melalui Smart TV Memajukan Membaca Permulaan Pada Siswa Lamban Belajar - Agustinus Luther Tibe; Pujaningsih Pujaningsih (Academia Open, 2026)
General Background Early reading proficiency, specifically decoding and blending phonemes into meaningful words, represents a fundamental literacy milestone in elementary education. Specific Background First-grade students at risk of being slow learners frequently struggle with grapheme-phoneme correspondence and syllable blending, resulting in significantly low reading accuracy for foundational consonant-vowel (CV-CV) patterned words. Knowledge Gap While explicit phonics and digital media are individually recognized as beneficial, there remains limited classroom action research integrating Smart TV-assisted multisensory phonics with systematic segmenting, blending, and prompt fading to support these specific at-risk learners. Aims This Classroom Action Research study describes the implementation of Smart TV-assisted multisensory phonics instruction and investigates its capacity to elevate the meaningful CV-CV word reading proficiency of two first-grade students at risk of slow learning at SDN 007 Malinau Selatan Hilir. Results Following a two-cycle intervention, average reading accuracy progressed from a 44% baseline to 62% in Cycle I, ultimately achieving 85.5% in Cycle II, thereby surpassing the 80% mastery criterion. Concurrently, student engagement reached 93.49% and teacher instructional fidelity attained 97.40%. Novelty This study uniquely demonstrates that combining structured repetition and visual-auditory prompting exclusively through a synchronized Smart TV platform successfully resolves severe early decoding deficits. Implications Educational institutions and educators must prioritize structured, technology-mediated phonics interventions to scaffold early literacy acquisition, ensuring sustainable academic progression for at-risk student populations. Highlights Smart TV-assisted multisensory phonics instruction significantly elevates early word decoding proficiency. Average consonant-vowel reading accuracy escalated from a 44% baseline to 85.5%. Explicit visual-auditory prompting and structured repetition successfully bridge early literacy deficits. Keywords Early Literacy Acquisition; Multisensory Phonics; Slow Learners; Smart TV; Classroom Action Research